Ekström, Anette - (:unkn) unknown (My University, 2026)
Anette Ekström is a Nurse and Midwife and an Associate professor in Nursing at the University of Skövde, Sweden. She received a Registered Nurse Degree (1979) from the Department of Health Sciences, University of Skövde, a Registered Midwife Degree (1988) from the Department of Health Sciences, University of Skövde, a Ph.D. degree (2005) in Reproductive and Perinatal Health from the Karolinska University, Stockholm, Sweden and an Associate Professor degree (2011) in Nursing. Her research interest is within the fields of Care science that include Nursing, Reproductive, Perinatal and Sexual Health, as well as Public Health. (Support during childbirth and breastfeeding as well as Development of instruments and methods and Complementary and Alternative Methods). She is a part of the Executive Editor of Journal of Nursing & Care.(2012-still) and a Lead Guest Editor in an special issue in Nursing Research and Practice (2012-still).